A Meta‐Analysis of the Relationship between Mathematics Achievement and Creativity. (21st October 2020) - Bicer, Ali; Chamberlin, Scott; Perihan, Celal
Abstract: In the current investigation, research studies ( n  = 30) conducted from 1965 to 2018 were synthesized to examine the mathematics achievement–creativity relationship and the range of factors that could have moderated this relationship. The meta‐analysis included sample size of 11, 418 and revealed that there was an overall moderate and statistically significant ( r  = 0.47, p  < .05) positive correlation between mathematics achievement and creativity. The investigation further revealed that the relationship was constant across sample location but stronger when the relationship was examined with mathematical creativity ( r  = 0.53, p < .05) than with general creativity. Findings from studies conducted after 2000 indicated a stronger relationship between general creativity and mathematics achievement than did findings from studies conducted before 2000. The relationship was the strongest when creativity was measured through the Mathematical Creativity Test (MCT) compared to other measures of general or mathematical creativity. Lastly, the relationship was stronger for elementary and middle school students than for high school students. Possible explanations for these findings in relation to existing theories and the implications for future research are provided.